If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-4(8))(-30) + -1(-8) = x Multiply -4 * 8 (-32)(-30) + -1(-8) = x Multiply -32 * -30 960 + -1(-8) = x Multiply -1 * -8 960 + 8 = x Combine like terms: 960 + 8 = 968 968 = x Solving 968 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 968 + -1x = x + -1x Combine like terms: x + -1x = 0 968 + -1x = 0 Add '-968' to each side of the equation. 968 + -968 + -1x = 0 + -968 Combine like terms: 968 + -968 = 0 0 + -1x = 0 + -968 -1x = 0 + -968 Combine like terms: 0 + -968 = -968 -1x = -968 Divide each side by '-1'. x = 968 Simplifying x = 968
| 2/15=21/15 | | -3-x/4=-x | | 40=1.6u | | -13+23=-2(x+3) | | 3x-2/5 | | 3x-2/5=21/15 | | -9-4-19= | | 9=9x-10 | | 172-x=234 | | -10-2x=10 | | 5/2=4/x | | 7/3-x/7 | | -9x/5=18 | | -40/(-12-8) | | y/5=y/4+4 | | 3-x+4-16=-2X+14-6 | | -2(18-3y)=7y+27 | | y/5=y/4+5 | | 3/11x+13=20 | | y/2.5=8 | | 4x+4(x+10)=480 | | 8x-44=6x-6 | | 274=-x+33 | | 18x-9=5x-1+3x | | 7+4(-6)= | | x=v-10 | | 31=6y+2x | | 26-w=209 | | x/2-9/10=x/5 | | T=1/6(x-y+z) | | 7w/6+3=5w/4 | | 6x-3+2x+1/3+4x/3=0 |